Permeability Enhancement of Coal Seam by Lower Protective Layer Mining for Gas Outburst Prevention - Aiping He; Hua Fu; Bingjie Huo; Chaojun Fan (Shock and Vibration)
Risk prediction of dynamic disasters such as rock burst, gas outburst, and water inrush is closely related to the permeability evolution of coal seam. According to the characteristics of the lower protective layer mining, the basic assumption of gas-solid coupling model of the coal was proposed in this paper. The permeability enhancement coefficient of equivalent layer spacing was first put forward. Based on the three-zone-shaped dynamic evolution of the permeability of the overlying protective layer during the lower protective layer mining, the theories of seepage mechanics and damage mechanics were applied to introduce the permeability enhancement coefficient of equivalent layer spacing. A mathematical model of permeability evolution of the protected coal seam in the lower protective layer mining was established. Based on the engineering background of the lower protective layer mining in Changping Coal Mine, the numerical simulation using the proposed mathematical model was performed. The results showed that the stress and permeability of the protected layer in #3 coal seam evolved dynamically with the advancement of the working face of the protective layer in #8 coal seam. When the working face of the protective layer in #8 coal seam advanced to 80 m, the stress reduction rate in the relief area tended to be stable, and the stress in the stress reduction area was about 50% of the original rock stress. When advanced to 80 m, the permeability of the protected layer of the #3 coal seam increased sharply, and the permeability increased by 873 times. With the continuous advancement, the permeability of the protected layer in #3 coal seam tended to increase steadily, and the permeability increased by 1100–1200 times. The calculated magnitude of permeability increment is consistent with that in the engineering practice, indicating that the permeability evolution model is basically reasonable. The research provides a theoretical guidance for the gas drainage field application in the lower protective layer mining for prevention of coal and gas outburst.